PRODUCTION OF CELLULOSE ACETATE MEMBRANE FROM COCOA (THEOBROMA CACAO L) SHELL MODIFIED POLYETHYLENE GLICOL FOR PB METAL ION FILTRATION - Riani, Pevi; Syafrinal; Ikhlas Armin, Muhammad (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
In this study, a modified polyethylene glycol modified cellulose acetate membrane was made. Cellulose acetate was synthesized from cocoa husk waste (Theobroma cacao L) with several steps, namely isolation of alpha cellulose from cocoa husk waste, synthesis of cellulose acetate from alpha cellulose, preparation of 10% cellulose acetate membrane with the addition of polyethylene glycol 0, 5, 10, 15, 20 & 25% . From the results of the research, it was found that the FT-IR analysis of -cellulose from cocoa shells showed an absorption peak at wave numbers between 3400 – 3500 cm-1 which indicated the presence of O-H stretch groups. At wave numbers 2800-2900 cm-1 indicates C-H stretching, then it can be seen at wave numbers 1160 cm-1 indicates C-O-C stretching, and at 1035-1060 cm-1 indicates C-O stretching. In the fingerprint area, we found absorption peaks at wave numbers around 1300 cm-1 which indicated the presence of C-H bending and around 1400 cm-1 indicating the presence of CH2 bending. The cellulose acetate obtained is white and smooth compared to alpha cellulose. At the membrane preparation stage, the results of the insoluble cellulose acetate & PEG using acetone as a solvent. So it is necessary to do a solubility test and find a suitable solvent to form polyethylene glycol modified cellulose acetate membrane for Pb metal ion filtration.